Alloy, alloy member and method for producing alloy member
A Ta, Nb, and Mo-based alloy with Ti, Hf, or Ni, formed through melt solidification in an inert gas, addresses the issue of corrosion resistance in reactive environments, offering superior protection against chlorine and bromine with a corrosion rate of 0.1 mm/year or less and high hardness.
Patent Information
- Application Number
- JP2024118683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-25
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-06
AI Technical Summary
Existing alloys and coatings used for corrosion resistance in semiconductor manufacturing and reactive environments suffer from low toughness and inadequate resistance to reactive substances like chlorine and bromine, leading to corrosion and mechanical failure.
An alloy comprising Ta, Nb, and Mo as the first element group, and at least one of Ti, Hf, and Ni as the second element group, with specific atomic percentages, combined with a melt solidification process in an inert gas atmosphere to form a dendrite structure, enhancing corrosion resistance and hardness.
The alloy achieves excellent corrosion resistance to reactive substances such as chlorine and bromine, with a corrosion rate of 0.1 mm/year or less, and high hardness, suitable for semiconductor manufacturing and plant equipment components.
Smart Images

Figure 2025019012000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an alloy having excellent corrosion resistance, for example an alloy having excellent corrosion resistance to chlorine and the like, an alloy member, and a method for producing the alloy member. [Background technology]
[0002] Semiconductor chips are obtained by thinning a semiconductor wafer to a predetermined thickness in a back-grinding process, an etching process, etc., and then dividing the wafer into individual chips through a dicing process. During this process, the semiconductor wafer is repeatedly subjected to a lamination process in which each layer is laminated in a chamber, and an etching process in which parts are partially removed by etching, etc.
[0003] In these lamination and etching processes, highly reactive substances are used. However, many of these reactive substances are also highly corrosive. For example, there are gases and solutions that contain chlorine or bromine. These reactive substances can affect and corrode not only the semiconductor wafer, but also the pipes and chambers of the semiconductor manufacturing equipment.
[0004] In addition, petrochemical plants, chemical plants, water treatment plants, and incineration facilities also handle reactive substances such as chlorine, so materials that are resistant to corrosion are desired. For example, Al 2 O 3 A method has been proposed in which the surfaces of the various parts inside the chamber are coated with ceramics such as AlN and TiN (for example, Patent Document 1).
[0005] On the other hand, high entropy alloys (HEAs) have been known as alloy materials with high corrosion resistance. For example, HEAs containing Nb and Mo and at least two of Ta, W, Ti, Hf, and Zr have been proposed as alloys with resistance to aluminum alloys (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-72110 A [Patent Document 2] WO2021 / 193529 publication Summary of the Invention [Problem to be solved by the invention]
[0007] However, when corrosion resistance is improved by using a corrosion-resistant ceramic coating or the like, the coating is a thin film with low toughness, and there is a problem that the coating partially peels off due to aging caused by mechanical action with reactive substances. On the other hand, technical studies are being conducted to improve corrosion resistance using HEA, but further improvement in corrosion resistance against reactive substances such as chlorine is desired. Therefore, the present invention aims to provide an alloy, an alloy member, and a method for manufacturing an alloy member that are excellent in corrosion resistance against reactive substances such as chlorine. [Means for solving the problem]
[0008] The present invention is an alloy characterized in that a first element group includes Ta, Nb, and Mo, and a second element group includes at least one of Ti, Hf, and Ni, and when the total of the elements in the first element group and the second element group is 100 atomic %, the alloy contains Ta at 10 atomic % or more and 35 atomic % or less, Nb at 20 atomic % or more and 35 atomic % or less, Mo at more than 0 atomic % and 10 atomic % or less, and at least one of Ti, Hf, and Ni at 20 atomic % or more and 35 atomic % or less.
[0009] It is also preferable that the Ta and Nb are each contained in an amount of 20 atomic % or more and 35 atomic % or less, the Mo is contained in an amount of 5 atomic % or more and 10 atomic % or less, and the Ti is contained in an amount of 20 atomic % or more and 35 atomic % or less.
[0010] The present invention also relates to an alloy member comprising at least a portion of the above alloy.
[0011] The present invention also provides a method for producing an alloy member, which includes a melting and solidifying process in which a metal powder is discharged onto a substrate and irradiated with a heat source to melt and solidify the metal powder to form a solidified layer, and the melting and solidifying process is repeated, wherein the metal powder includes a first element group including Ta, Nb, and Mo, and a second element group including at least one of Ti, Hf, and Ni, and when the sum of the elements in the first element group and the second element group is taken as 100 atomic %, the Ta content is 10 atomic % or more and 35 atomic % or less, the Nb content is 20 atomic % or more and 35 atomic % or less, the Mo content is more than 0 atomic % and 10 atomic % or less, and at least one of Ti, Hf, and Ni is 20 atomic % or more and 35 atomic % or less.
[0012] The melting and solidifying step is preferably carried out in an inert gas atmosphere.
[0013] In addition, it is preferable to carry out the treatment while controlling the oxygen concentration in the inert gas atmosphere to be 100 ppm or less in vol %. Effect of the Invention
[0014] According to the present invention, it is possible to provide an alloy, an alloy member, and a method for manufacturing an alloy member, which have excellent corrosion resistance against reactive substances such as chlorine. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram of a dendritic structure. [Diagram 2] FIG. 1 is a schematic diagram of a directed energy deposition additive manufacturing device. [Diagram 3] FIG. 1 shows an electron reflection image and element mapping of the present Example F1B. [Figure 4] FIG. 13 is an enlarged view of elemental mapping of Ta in this embodiment F1B. [Diagram 5] FIG. 1 shows an electron reflection image and element mapping of F2B of this Example. [Figure 6] FIG. 13 is an enlarged view of elemental mapping of Ta in this embodiment F2B. [Figure 7] FIG. 2 shows an electron reflection image and element mapping of F3B in this embodiment. [Figure 8] FIG. 13 is an enlarged view of elemental mapping of Ta in this embodiment F3B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings.
[0017] First, the alloy will be described, and then the alloy member and the manufacturing method of the alloy member will be described. In the following description, % indicates atomic % (at.%). In this specification, a numerical range expressed using "~" means a range including the numerical values written before and after "~" as the lower limit and upper limit. The lower limit and upper limit of the numerical range can be appropriately combined.
[0018] <Alloy> In the alloy of this embodiment, when the total of the constituent elements is 100%, the content of each constituent element is at most 35 atomic %, and it can be recognized as a type of HEA. It is known that HEA has characteristics such as (a) stabilization of the mixed state due to a negative increase in the mixing entropy term in the Gibbs free energy equation, (b) delay in diffusion due to a complex microstructure, (c) improvement of mechanical properties due to high lattice distortion caused by the size difference of the constituent atoms, and (d) improvement of properties due to the combined effect (also called cocktail effect) of the coexistence of multiple elements, in which at least four major metal elements (each of which does not account for the majority, for example, in the range of 5 atomic % to 45 atomic %) are expressed.
[0019] However, in order to obtain corrosion resistance (sometimes referred to as corrosive gas resistance) against the halogen ions and radicals contained in the reactive substance, it is necessary to make the reactive substance less susceptible to reaction with chlorine ions, chlorine radicals, bromine ions, bromine radicals, etc. (hereinafter simply referred to as chlorine ions, etc.).
[0020] Therefore, in this embodiment, the first element group includes Ta, Nb, and Mo as elements resistant to chloride ions, and the second element group includes at least one of Hf, Ti, and Ni. The reasons for selecting each constituent element and its content will be explained below. The content of each constituent element is adjusted so that the sum of the first element group and the second element group is 100%.
[0021] (Ta:10%~35%) Ta is an element that has excellent corrosion resistance to chloride ions and the like, and can be contained in the range of 10% to 35%, preferably 20% to 35%, and more preferably 23% to 35%.
[0022] (Nb: 20% to 35%) Nb, like Ta, is an element that has excellent corrosion resistance to chlorine ions, etc. In addition to chlorine, Nb is also expected to have corrosion resistance to bromine. Therefore, it can be contained in the range of 20% to 35%, and more preferably in the range of 23% to 35%.
[0023] (Mo: more than 0% and less than 10%) Like Ta and Nb, Mo can be contained to improve corrosion resistance, and can be contained in the range of more than 0% to 10%, preferably in the range of 0.5% to 10%, and more preferably in the range of 5% to 10%.
[0024] (At least one of Ti, Hf and Ni is 20% or more and 35% or less each) In addition to the first element group consisting of Ta, Nb, and Mo, the second element group contains at least one of Ti, Hf, and Ni. Ti, Hf, and Ni are expected to have the effect of improving corrosion resistance, similar to Ta and Nb. For example, Hf is expected to have the effect of improving the hardness of the alloy. Therefore, at least one of Ti, Hf, and Ni is preferably contained in the range of 20% to 49%, more preferably in the range of 25% to 47%, and even more preferably in the range of 30% to 47%.
[0025] Also, it is more preferable that Ti is contained in the range of 20% to 35%, and even more preferable that it is contained in the range of 23% to 30%. By containing Ti, it is expected that the corrosion resistance to bromine is improved. Furthermore, when it is desired to improve the corrosion resistance to bromine in addition to chlorine, it is even more preferable that the total of Hf, Ti and Ni is 35% or less.
[0026] (Both Ti and Hf (total amount of Ti and Hf): 49% or less) When it is desired to further improve the corrosion resistance and hardness, it is preferable to contain both Ti and Hf from the second element group. When both Ti and Hf are contained, the upper limit of the total amount of Ti and Hf is preferably 49% or less, more preferably in the range of 20% to 49%, and further preferably in the range of 23% to 47%.
[0027] (Inevitable impurities) The alloy according to the present embodiment may contain unavoidable impurities as the balance of the above-mentioned constituent elements. For example, unavoidable elements such as C, N, O, and Zr may each be contained in an amount of 500 ppm or less by mass%. In addition, it is preferable to limit the total amount of unavoidable impurities to 1% or less by mass%. In particular, since Zr easily reacts with chlorine and bromine and may be easily corroded, it is preferable to limit it to 1% or less.
[0028] (Corrosion resistance) The alloy of this embodiment has excellent corrosion resistance. For example, it has excellent corrosion resistance against reactive gases (particularly gases containing chlorine ions, etc.) and reactive (corrosive) solutions (particularly solutions containing hydrochloric acid), which are reactive substances. The corrosion resistance can be evaluated by determining the corrosion degree and corrosion rate from the mass change of the alloy flakes before and after the test using a method of exposing the alloy flakes to a reactive gas atmosphere or a method of immersing the alloy flakes in a reactive solution.
[0029] The evaluation of corrosion resistance will be specifically described using the case of immersion in a reactive solution as an example. The corrosion resistance can be evaluated by a method of evaluating the degree of general corrosion by an immersion test. For example, when evaluating the corrosion resistance of chlorine, the alloy piece is immersed in a 5 mass% hydrochloric acid solution, and the 5 mass% hydrochloric acid solution is boiled and held for 24 hours, and the mass change of the alloy piece before and after the test is measured, and the mass (g) and surface area (mm 2 ) to obtain the corrosion rate (g / mm 2 / h) can be used to evaluate the
[0030] For example, when evaluating the corrosion resistance of bromine, the alloy piece is immersed in a 47 mass% hydrobromic acid solution, and the 47 mass% hydrobromic acid solution is heated to 60°C and held for 24 hours. The mass change of the alloy piece before and after the test is measured, and the mass (g) and surface area (mm 2 ) to obtain the corrosion rate (g / mm 2 / h) can be used to evaluate the
[0031] In addition, the corrosion rate (g / mm 2 The corrosion rate may be evaluated by converting the mass (g) of the alloy flakes before the test into the volume (mm 3 ) to obtain density (g / mm 3 ) and divide the corrosion rate by the density ((g / mm 2 / h) / (g / mm 3 ) multiplied by 24 (h) and 365 (days) to obtain the corrosion rate (mm / year).
[0032] The alloy of this embodiment can achieve a corrosion rate of 0.1 (mm / year) or less, and can even achieve a corrosion rate of 0.05 (mm / year) or less, and furthermore, 0.03 (mm / year) or less.
[0033] (Hardness) The hardness of the surface layer of the alloy or alloy member of this embodiment can be evaluated, for example, by Rockwell hardness HRC (hereinafter referred to as hardness) or Vickers hardness HV. The Rockwell hardness is preferably 13HRC or more, more preferably 20HRC or more, and even more preferably 25HRC or more. The Vickers hardness is preferably 200HV or more, more preferably 300HV or more, and even more preferably 350HV or more.
[0034] The Rockwell hardness can be measured, for example, by averaging three points excluding the maximum and minimum values when five measurements are taken, while the Vickers hardness can be measured, for example, by averaging five points excluding the maximum and minimum values when seven measurements are taken under conditions of a load of 0.5 kg and a load application time of 10 s.
[0035] (organization) The alloy structure of this embodiment may vary depending on the manufacturing method and manufacturing conditions, but typically has a dendritic structure. Figure 1 is a schematic diagram of one aspect of the dendritic structure. The dendritic structure mainly contains Ta, Nb, Mo, etc., and has a dendritic structure having a primary branch (primary arm) 1 extending along the solidification direction and a secondary branch (secondary arm) 2 extending from the primary branch 1. It is preferable that the dendritic structure is present in a uniformly dispersed state.
[0036] The solidification rate is said to be correlated with the secondary dendrite arm spacing of the structure, and the narrower the secondary arm spacing, the faster the solidification rate. A fast solidification rate narrows the dendrite width, which is expected to improve hardness. It is also assumed that corrosion will proceed preferentially from areas where Ti is segregated compared to the dendritic structure. Therefore, it is expected that the presence of a uniformly dispersed dendritic structure in the alloy structure will suppress the progression of corrosion.
[0037] The distance between adjacent secondary arms in a dendritic structure (the distance between the parts indicated by w in FIG. 1) is referred to as the secondary arm spacing. The secondary arm spacing w of a dendrite is preferably 6.0 μm or less. A secondary arm spacing w of 6.0 μm or less may be sufficient as long as it is present in a part of the dendritic structure, and the secondary arm spacing can be measured, for example, by the secondary branch method using a dendritic structure that can be confirmed in the observation field.
[0038] <Method of manufacturing alloy member> The alloy member of the present embodiment includes a melting and solidifying step in which a metal powder is discharged onto a base material and irradiated with a heat source to melt and solidify the metal powder to form a solidified layer, and the melting and solidifying step is repeated to produce the alloy member by a so-called additive manufacturing method.
[0039] (metal powder) The metal powder may be an alloy powder or a mixed powder obtained by mixing pure metal powders, which contains Ta, Nb, and Mo as the first element group, and at least one of Ti, Hf, and Ni as the second element group, and contains 10 atomic % or more and 35 atomic % or less of Ta, 20 atomic % or more and 35 atomic % or less of Nb, more than 0 atomic % and 10 atomic % or less of Mo, and at least one of Ti, Hf, and Ni, respectively, when the total of the elements of the first element group and the second element group is taken as 100%. Hereinafter, a method for manufacturing an alloy member will be described taking the case where a mixed powder obtained by mixing pure metal powders is used as an example.
[0040] A predetermined amount of pure metal powder of each element is measured so as to obtain an alloy with a predetermined composition range, and these are mixed to produce a mixed powder. The mixed powder obtained is irradiated with an electron beam or laser beam, which is a heat source, and additive manufacturing is performed by melting and solidifying it. In one embodiment, the method can be applied to both powder bed fusion (PBF) and directed energy deposition (DED), which are additive manufacturing methods for metal materials.
[0041] The powder particle size may be adjusted by mesh sieving or airflow classification according to the modeling method of the additive manufacturing method. For example, the modeling powder used in the powder bed fusion method using an electron beam or laser beam must be melted by the laser beam, which serves as the heat source, while removing coarse powder that is difficult to melt in order to minimize the range of heat influence. In addition, in order to obtain optimal fluidity to ensure the laying of the powder, it is also necessary to remove highly adhesive fine powder.
[0042] For example, when applied to powder bed fusion (PBF), it is preferable to use metal powder with an average particle size (D50) adjusted to the range of 10 to 60 μm. For example, metal powder used in directed energy deposition must have coarse powder that is difficult to melt removed in order to melt the powder with a laser beam that serves as a heat source. In addition, fine powder must also be removed in order to prevent dust scattering when the powder is supplied to the heat source and to ensure flowability that allows the powder to be easily transported.
[0043] For this reason, when applied to directed energy deposition, it is preferable to use a material with an average particle size (D50) adjusted to the range of 50 to 300 μm. Furthermore, when using an electron beam or plasma as a heat source, it becomes possible to mold using coarser metal particles, so it is preferable to set the average particle size (D50) to 75 to 250 μm.
[0044] An additive manufacturing method will be described below by taking a directed energy deposition method as an example of an embodiment of a manufacturing method for an alloy member. FIG. 2 shows a schematic configuration of an additive manufacturing apparatus 100 using a directed energy deposition method. The additive manufacturing apparatus 100 is mainly composed of a powder supply nozzle 116, a focus lens 112, a protective lens 114, and the like. Metal powder 120 is supplied to the powder supply nozzle 160 and sprayed to the tip of the powder supply nozzle 116 together with an inert gas as a shielding gas 180. A laser beam 110 emitted from a laser oscillator (not shown) is focused by the focus lens 112 and irradiated near the tip of the powder supply nozzle 160. A protective lens 140 is provided below the focus lens 112.
[0045] In the additive manufacturing method using the directed energy deposition method, a powder supply nozzle 116 is moved relative to a substrate 150 while supplying a metal powder 120 onto the substrate 150. A laser beam 110 focused by a focus lens 120 is irradiated onto the supplied metal powder 120, and the metal powder 120 is melted to form a molten pool 130, which is then solidified to form an additively manufactured object 140 (alloy or alloy component). This process is repeated using a program file created using CAD-CAM software to stack the additively manufactured object 140 on the substrate 150, thereby forming a three-dimensional alloy component having an alloy at least in a part thereof.
[0046] Here, in the melting and solidifying process in which the metal powder 120 is discharged onto the substrate 150 and irradiated with the laser beam 110 as a heat source to melt and solidify the metal powder 120 to form a solidified layer, it is preferable to perform the melting and solidifying process in a state in which an inert gas atmosphere is formed locally around at least the periphery of the molten pool 130 where the metal powder 120 and the laser beam 110 converge, by spraying a constant amount of shielding gas or controlling the flow rate.
[0047] In another embodiment, additive manufacturing is preferably performed in an inert gas atmosphere with an oxygen concentration of 100 ppm or less by vol%. For example, the powder supply nozzle 116, the metal powder 120, and the additively manufactured object 140 may be placed in a sealable space such as a chamber of the additive manufacturing apparatus 100, and the atmosphere may be partially replaced with an inert gas atmosphere. By performing additive manufacturing in a space replaced with an inert gas atmosphere, it is expected that beads will be stably formed, thereby reducing defects in the additively manufactured object 140.
[0048] [Additive manufacturing conditions] The additive manufacturing conditions are determined appropriately taking into consideration the particle size and composition of the raw material powder, the size and shape of the shaped body, characteristics, production efficiency, etc., but for the alloy of this embodiment, they can be selected, for example, from the following ranges.
[0049] The thickness of one layer during additive manufacturing can be, for example, 0.1 mm to 10.0 mm, and is preferably 0.1 to 5.0 mm. The thickness of the first layer alloy formed on the surface of the substrate (the thickness from the interface of the base material to the surface of the first layer alloy, including the dilution layer near the interface) is preferably 0.1 mm to 10 mm. Here, the dilution layer refers to a layer in which the first layer alloy melts with the base material when shaping the first layer alloy, and the compositions of both the base material and the first layer alloy are mixed.
[0050] Next, the laser output (W) is preferably 1500 to 5000 W, more preferably 1500 to 2500 W. The laser scanning speed (mm / min) is preferably 500 to 2000 mm / min, more preferably 500 to 1800 mm / min. The powder supply amount (g / min) is preferably 10 to 20 g / min, more preferably 14 to 18 g / min. The laser spot diameter (d) is preferably 0.5 to 10 mm, more preferably 1 to 5 mm.
[0051] The density of the energy input by laser irradiation to melt the mixed powder (energy density of the heat source: J / mm 2) has the effect of suppressing the increase in the defect rate, preventing the supplied powder from becoming difficult to melt, and preventing the base material or additive manufacturing body in a wide range centered on the laser irradiation position from melting, and is expected to maintain the shape of the model. 2 is preferable, and 10 to 300 J / mm 2 The range of the energy density E (J / mm 2 ) can be calculated using the laser output P (W), laser scanning speed v (mm / min), and laser spot diameter (d) as E = (P / vd) x 60.
[0052] [Application] Applications of the alloy of this embodiment or an alloy member at least partially comprising the alloy of this embodiment include, for example, members placed in a corrosive fluid (gas) environment, members placed in a liquid containing chlorine, members of equipment or devices exposed to or immersed in reactive substances, etc. In addition, highly reactive substances such as chlorine and bromine are used in catalysts in petrochemical plants and chemical plants, disinfectants in water treatment plants, and incineration facilities, so the alloy of this embodiment can be used as a member of these equipment or devices.
[0053] Furthermore, an alloy component that contains at least a portion of the alloy of this embodiment has both corrosion resistance and hardness, making it possible to construct severely corroded components as corrosion-resistant structures. In addition, because of its high hardness, effective corrosion resistance can be achieved even with a reduced amount of coating agent, for example by applying a surface coating agent only to the severely corroded parts.
[0054] (Example) The additive manufactured bodies F1 to F4 produced in this embodiment will be described below. Using a three-dimensional additive manufacturing device using a directed energy deposition (DED) method, the additive manufactured bodies F1 to F4 with a width of 20 mm, a length of 20 mm, and a stacking height of approximately 10 mm were produced. Table 1 shows the constituent elements and the contents of the constituent elements (alloy composition) of the additive manufactured bodies F1 to F4.
[0055] The metal powders used were Nb powder (particle size distribution range: 75-150 μm), Hf powder (particle size distribution range: 50-100 μm), and Mo powder (particle size distribution range: 150 μm or less) manufactured by Kojundo Chemical Co., Ltd., Ti powder (particle size distribution range: 45-106 μm) manufactured by Carpenter Additive, Ta powder (particle size distribution range: 45-105 μm) manufactured by Taniovis Japan, and Ni powder (particle size distribution range: 45-90 μm) manufactured by Hoeganaes, and were adjusted to the desired alloy composition using the method described below.
[0056] [Table 1]
[0057] In order to simultaneously spray each metal powder from the powder supply nozzle, the supply amount of each powder was adjusted so that it was within the composition range in Table 1, the resulting mixed powder was sprayed from the powder supply nozzle toward the substrate, and the sprayed mixed powder was irradiated with a laser as a heat source to melt and solidify it, and this process was repeated to create an additive manufacturing object. The supply amount of each powder was adjusted so that the total of all powders was 14 g / min.
[0058] [Table 2]
[0059] As shown in Table 1, additive product F1 contains 10 atomic % Mo, 30 atomic % each of Ta, Nb, and Hf. F2 contains 6 atomic % Mo, 23.5 atomic % Ta, Nb, Hf, and Ti. F3 contains 10 atomic % Mo, 30 atomic % each of Ta, Nb, and Ti. F4 contains 6 atomic % Mo, 23.5 atomic % Ta, Nb, Ni, and Ti.
[0060] (Formability evaluation) The constituent elements of F1 to F4 and the contents of those elements were not changed, and the formability was evaluated when the atmosphere during additive manufacturing (modeling) was air or argon. The formability evaluation results are shown in Table 3. In Table 3, among the additive manufactured objects produced in air, those produced using the additive manufacturing device LT65 (manufactured by DMG-MORI) are indicated with a sample number ending in A, and those produced using the additive manufacturing device LAMUDA200 (manufactured by Nidek Machine Tools) are indicated with a sample number ending in C.
[0061] The additive manufactured products produced under an argon atmosphere were manufactured using an additive manufacturing device, LAMUDA200 (manufactured by Nidek Machine Tools). A chamber was set up to house the base material, powder supply nozzle, laser head, etc., and the atmosphere inside the chamber was replaced with argon gas. The sample number was indicated by the letter B at the end.
[0062] Additively manufactured bodies F1A to F4A have in common the following additive manufacturing conditions: a stainless steel substrate was used, the thickness of one layer during additive manufacturing was approximately 1.5 mm, the laser beam diameter (laser spot diameter) was approximately 2 mm, argon gas was used as the shielding gas, and the flow rate of the shielding gas was set to 35 to 53 L / min. Only when additive manufacturing was performed under an argon atmosphere, an oxygen concentration meter was installed approximately 1 m above the substrate to measure the oxygen concentration (vol%) before the start of additive manufacturing and after the completion of additive manufacturing.
[0063] [Table 3]
[0064] As shown in Table 3, the additive manufacturing product F2C showed significant oxidation of elements highly reactive with air. With the composition of F2, it is possible to model in air, although it is necessary to adjust the conditions, and it is thought that more stable modeling can be achieved under an inert gas atmosphere. In this regard, it was confirmed that more stable modeling can be achieved by replacing the atmosphere during modeling (melting and solidification process) with argon gas, as in the additive manufacturing conditions for F2B, and by controlling the oxygen concentration of the atmosphere to be 100 ppm or less in vol%.
[0065] In this way, the alloy according to this embodiment can be applied to an alloy part that contains the alloy at least in part (for example, the surface of a base material), and to a product that includes the alloy part at least in part.
[0066] (Corrosion resistance) Next, corrosion resistance to chlorine was evaluated using a boiling hydrochloric acid immersion test. In the boiling hydrochloric acid immersion test, test pieces (10 x 10 x 2 (mm)) cut from additive manufactured bodies F1A, F1B, F2A, F2B, F3A, and F3B, and a test piece (18 x 18 x 2 (mm)) cut from F4A were immersed in a 5 mass% hydrochloric acid (HCl) test solution, the 5 mass% hydrochloric acid test solution was boiled on a hot plate, and the boiling state was maintained while the pieces were immersed continuously for 24 hours. The mass change (g) of the test pieces before and after the immersion test (also simply referred to as before and after the test) was calculated based on the surface area (mm 2 ) and the corrosion rate (g / mm 2 / h) was calculated, and the corrosion rate (mm / year) was calculated from the obtained corrosion degree and evaluated.
[0067] Additionally, the corrosion resistance to bromine of additive manufactured products F3A and F4A was evaluated using a hydrobromic acid immersion test. A test piece (18 x 18 x 2 (mm)) cut from additive manufactured product F3A and a test piece (18 x 18 x 2 (mm)) cut from additive manufactured product F4A were each immersed continuously for 24 hours in a 47 mass% hydrobromic acid (HBr) solution with the liquid temperature held at 60°C. Based on the results of the mass measurements before and after the immersion test, the mass change (g) was calculated as a function of the surface area (mm 2 ) and the corrosion rate (g / mm 2The corrosion rate (mm / year) was calculated from the corrosion degree obtained and evaluated. Tables 4 and 5 show the results of the boiling hydrochloric acid immersion test and the hydrogen bromide immersion test.
[0068] [Table 4]
[0069] [Table 5]
[0070] As shown in Tables 4 and 5, the corrosion rates calculated from the results of the 5 mass% boiling hydrochloric acid immersion test for additive manufactured bodies F1A, F1B, F2A, F2B, F3A, F3B, and F4A were confirmed to have excellent corrosion resistance with a corrosion rate of 0.04 mm / year or less. Furthermore, the results of the 47 mass% hydrogen bromide immersion test confirmed that F3A had excellent corrosion resistance with a corrosion rate of 0.002 mm / year. As a conventional example, a similar evaluation was performed on a material equivalent to MAT21, which is a Ni-Cr-Mo light alloy, and the corrosion rate calculated from the 5 mass% boiling hydrochloric acid immersion test was 0.825 mm / year, and the corrosion rate calculated from the 47 mass% hydrobromic acid immersion test was 0.100 mm / year. A similar evaluation was also performed on SUS316L, and the corrosion rate calculated from a 47 mass% hydrobromic acid immersion test was 5.06 mm / year.
[0071] From the above, it was confirmed that an alloy containing Ta of 10% to 35%, Nb of 20% to 35%, Mo of more than 0% to 10%, and at least one of Ti, Hf, and Ni of 20% to 35% has excellent corrosion resistance against reactive substances such as reactive solutions.Furthermore, it was confirmed that an alloy containing Ta and Nb of 23.5% to 35%, Mo of more than 0% to 10%, at least Ti of Ti, Hf, and Ni of 20% to 35%, and the total of Hf, Ti, and Ni is 35% or less has excellent corrosion resistance against bromine as well as chlorine.
[0072] In addition, the Rockwell hardness of the additive manufactured bodies F1A, F1B, F2A, and F2B was measured, and the Vickers hardness of the additive manufactured bodies F2A, F2B, F3A, and F4A was measured. The results are shown in Table 6. As shown in Table 6, it was confirmed that F1A, F1B, F2A, and F2B have a Rockwell hardness of 27.0HRC or more, and F2A, F2B, F3A, and F4A have a Vickers hardness of 370HV or more. Furthermore, it was confirmed that F4A, an alloy containing Ta, Nb, Ti, and Ni in an amount of 20% or more and 45% or less, and Mo in an amount of 0% or more and 10% or less, has a Vickers hardness of 393HV, making it more suitable for applications requiring hardness in addition to corrosion resistance against reactive substances.
[0073] [Table 6]
[0074] It was confirmed that the additive manufacturing bodies F1 to F4 produced above have excellent corrosion resistance against highly reactive substances such as chlorine, and furthermore, can be used as alloy members with suitable hardness when applied as components for semiconductor manufacturing equipment and various plant facilities. In addition, by achieving both corrosion resistance and hardness, it is possible to configure highly corroded parts as corrosion-resistant structures, and because of the high hardness (strength), it is possible to reduce the amount of the material used and achieve effective corrosion resistance, such as by forming a surface coating only on the severely corroded parts.
[0075] Next, the evaluation results of the alloy structure will be explained using additively manufactured products F1B, F2B, and F3B as examples. The alloy structure was evaluated by acquiring electron reflection images and performing elemental analysis using an electron probe microanalyzer (EPMA, JEOL Ltd. JXA-8530F). The elements detected in the elemental analysis were Ta, Nb, Mo, Hf, Ti, C, and O. Figure 3 shows the electron reflection images and element distribution mapping diagrams of F1B, Figure 5 shows F2B, and Figure 6 shows F3B.
[0076] In addition, as shown in Figure 4, it was confirmed that F2B has some areas where Ta is concentrated. In addition, as shown in Figure 5, it was confirmed that F3B has some areas where Ta and Nb are concentrated.
[0077] In addition, Figure 4 is an enlarged view of the dashed frame shown in Figure 3(d), Figure 6 is an enlarged view of the dashed frame shown in Figure 5(d), and Figure 8 is an enlarged view of the dashed frame shown in Figure 7. As shown in Figures 4, 6, and 8, it was confirmed that F1B, F2B, and F3B all have a dendritic structure 6, and the secondary arm spacing is 6.0 μm or less. It is presumed that the hardness can be increased because the secondary arm spacing of the dendritic structure is 6.0 μm or less, that is, the dendritic structure is fine. It was also confirmed that the dendritic structure contains Nb and the like in addition to Ta.
[0078] 1: Primary arm 2: Secondary arm 6: Dendrite structure 100: Additive manufacturing equipment 110: Laser beam 112: Focus lens 114: Protective lens 116: Powder supply nozzle 120: Metal powder 130: Molten pool 140: Additive Manufacturing 150: Base material 180: Shielding gas
Claims
1. A first element group includes Ta, Nb, and Mo; The second element group includes at least one of Ti, Hf, and Ni, When the total of the elements of the first element group and the second element group is 100 atomic %, The Ta content is 10 atomic % or more and 35 atomic % or less, The Nb content is 20 atomic % or more and 35 atomic % or less, The Mo content is more than 0 atomic % and 10 atomic % or less, An alloy comprising at least one of Ti, Hf and Ni in an amount of 20 atomic % or more and 35 atomic % or less.
2. The Ta and Nb each contain 20 atomic % or more and 35 atomic % or less, The Mo content is 5 atomic % or more and 10 atomic % or less, The Ti content is 20 atomic % or more and 35 atomic % or less. The alloy of claim 1.
3. An alloy member comprising at least a part of the alloy according to claim 1 or 2.
4. A melting and solidifying step is performed by discharging a metal powder onto a substrate and irradiating the substrate with a heat source to melt and solidify the metal powder to form a solidified layer. The melting and solidifying process is repeated, The metal powder is A first element group includes Ta, Nb, and Mo; The second element group includes at least one of Ti, Hf, and Ni, When the total of the elements of the first element group and the second element group is 100 atomic %, The Ta content is 10 atomic % or more and 35 atomic % or less, The Nb content is 20 atomic % or more and 35 atomic % or less, The Mo content is more than 0 atomic % and 10 atomic % or less, A method for producing an alloy member, comprising the steps of: containing at least one of Ti, Hf, and Ni in an amount of 20 atomic % or more and 35 atomic % or less.
5. The method for producing an alloy member according to claim 4, wherein the melting and solidifying step is carried out in an inert gas atmosphere.
6. 6. The method for producing an alloy member according to claim 4, wherein the oxygen concentration in the inert gas atmosphere is controlled to be 100 ppm or less in vol %.
Citation Information
Patent Citations
Process chamber for semiconductor production equipment
JP2004072110A
Alloy and member
WO2021193529A1